Water footprint of a dairy production system in Costa Rica - Coto Fonseca, Alberto (2026)
Water management optimization is imperative in a sustainable productive system, and the production of dairy is no exception. However, in Costa Rica there is little information regarding the quantity of water consumed during milk production. This study generated the first water footprint assessment of a productive system of milk in the country on a monthly basis using the Water Footprint Network methodology. The water footprint was calculated in terms of volume of water required to produce one kg of fat- and protein-corrected milk (FCPM) and is comprised of three components: the water requirement of crops due to evapotranspiration (green water), consumed water incorporated in the production of milk (blue water) and the water required to dilute pollutants found in the wastewater of the dairy production system (grey water). Samples of wastewater were obtained from the third sedimentation tank of the dairy production system so the concentration of phosphates and total nitrogen could be determined and used in the grey water component. This temporal approach allowed the identification of both high- and low-water consumption months of the dairy farm. The total monthly water footprint ranged from 902.14 to 1226.75 L/kg FCPM for phosphates, whereas the range for total nitrogen oscillated between 903.95 and 1219.86 L/kg FCPM. The months with higher water footprint values were January, February, and December for both cases. The data and analyses presented herein are extremely important in Costa Rica to have a broader sense of water consumption in milk production regions across the country.